Pengaruh Budaya Organisasi Terhadap Semangat Kerja Karyawan Pada PT. Federal International Finance Group Cabang Bima - Jalaludin Aslam; Ita Purnama (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
This research was conducted at PT. Federal International Finance Group Bima Branch. With the aim to determine the influence of organizational culture on employee morale at PT. Federal International Finance Group Bima Branch. The population in this study are all employees at PT. Federal International Finance Group Bima Branch as many as 76 employees while the sample in this study were 46 employees. Analysis of the data used is the validity test, reliability test, simple linear regression test, correlation coefficient test, test the coefficient of determination, and partial t test. The results of this study are that the organizational culture variable has a significant effect on employee morale at PT. Federal International Finance Group Bima Branch.